Borcalein: a Carborane‐Based Analogue of Baicalein with 12‐Lipoxygenase‐Independent Toxicity. (11th November 2021) - Kuhnert, Robert; Kuhnert, Lydia; Sárosi, Menyhárt‐B.; George, Sven; Draca, Dijana; Paskas, Svetlana; Hofmann, Bettina; Steinhilber, Dieter; Honscha, Walther; Mijatović, Sanja; Maksimović‐Ivanić, Danijela; Hey‐Hawkins, Evamarie
Abstract: 12‐Lipoxygenase is crucial for tumour angiogenesis. 5, 6, 7‐Trihydroxy‐2‐phenyl‐4 H ‐1‐benzopyran‐4‐one (baicalein) is a suitable inhibitor for this enzyme but is rapidly metabolised in vivo . Thus, an improvement of the metabolic stability is necessary to enhance the therapeutic efficiency. An emerging approach to enhance metabolic stability of carbon‐based pharmaceuticals is the use of metabolically stable, non‐toxic boron clusters, such as dicarba‐ closo ‐dodecaborane(12)s (carboranes) as phenyl mimetics. Therefore, the unsubstituted phenyl ring of baicalein was replaced by meta ‐carborane, resulting in borcalein, the carborane analogue of baicalein. This substitution resulted in a decreased inhibitory activity toward 12‐lipoxygenase, but led to increased toxicity in melanoma (A375, B16, B16F10) and colon cancer cell lines (SW480, HCT116, CT26CL25) with decreased tumour selectivity in comparison to baicalein. Surprisingly, borcalein displays a different mechanism of cytotoxicity with increased intracellular production of reactive oxygen species (ROS), reactive nitrogen species (RNS) and nitric oxide (NO). Abstract : Putting the brakes on tumour invasion : Borcalein, a carborane‐based analogue of baicalein, was synthesised and investigated. The replacement of the phenyl moiety by meta ‐carborane led to decreased inhibitory activity toward 12‐lipoxygenase, but to increased toxicity toward melanoma (A375, B16, B16F10) and colon cancer cell lines (SW480, HCT116, CT26CL25) via increased intracellular production of nitric oxide and reactive oxygen species.